2015
DOI: 10.1093/jb/mvv095
|View full text |Cite
|
Sign up to set email alerts
|

Ethrel-stimulated prolongation of latex flow in the rubber tree (Hevea brasiliensisMuell. Arg.): an Hev b 7-like protein acts as a universal antagonist of rubber particle aggregating factors from lutoids and C-serum

Abstract: Ethrel-stimulated prolongation of latex flow in the rubber tree (Hevea brasiliensis Muell. Arg.): an Hev b 7-like protein acts as a universal antagonist of rubber particle aggregating factors from lutoids and C-serum

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 27 publications
0
13
0
Order By: Relevance
“…It was also shown that a 44 kDa C-serum protein could inhibit rubber particle aggregation caused by hevein [29]. This Hev b 7-like protein with an anti-aggregation effect is likely to be the antagonist factor previously identified in the C-serum as CS-HLLBP [27], and may also be related to the rubber synthesis inhibitor (m/s 43,700 Da) previously identified by Faridah Yusof et al in 1998 [123].…”
Section: Accepted Manuscriptmentioning
confidence: 70%
See 4 more Smart Citations
“…It was also shown that a 44 kDa C-serum protein could inhibit rubber particle aggregation caused by hevein [29]. This Hev b 7-like protein with an anti-aggregation effect is likely to be the antagonist factor previously identified in the C-serum as CS-HLLBP [27], and may also be related to the rubber synthesis inhibitor (m/s 43,700 Da) previously identified by Faridah Yusof et al in 1998 [123].…”
Section: Accepted Manuscriptmentioning
confidence: 70%
“…The rubber particle aggregation (RPA) inducing effect of hevein has more recently been confirmed [15,29]. It was also shown that a 44 kDa C-serum protein could inhibit rubber particle aggregation caused by hevein [29].…”
Section: Accepted Manuscriptmentioning
confidence: 92%
See 3 more Smart Citations